A new perfluorinated peroxynitrate, CF3CF2CF2CF2OONO2. Synthesis,characterization and atmospheric implications - Bossolasco, Adriana Gabriela (2014)
CF3CF2CF2CF2OONO2was synthesized from the photolysis of CF3CF2CF2CF2I, in presence of NO2and O2.Alkyl peroxynitrates (CxF2x+1OONO2) could be formed in the atmospheric degradation of chlorofluorocar-bons, hydrofluorocarbons and hydrofluoroethers. We present here the synthesis and characterization (IRand UV absorption cross sections) of CF3CF2CF2CF2OONO2and its comparison with those correspondingto other perfluoro alkyl peroxynitrates. The thermal stability was studied as a function of total pressure(from 9.0 to 417 mbar) and temperature (from 283 to 293 K) using infrared spectroscopy. Kinetic param-eters measured for the thermal dissociation wereEa= (81 ± 4) kJ/mol andA= 4.8 1012. DFT calculationsat the B3LYP/6-311+G⁄level were used to explore the ground state potential energy surface. Geometricalparameters, conformer populations and vibrational spectra are presented. The calculated activationenergy was 81.3 kJ mol 1in excellent agreement with experimental results. Atmospheric implicationsare discussed.